A Study on Employee Motivation and Engagement with special reference to Ancillary Industries of BHEL, Tiruchirapalli - Dr. C. Suresh, B.Asha Daisy (International Journal of Advanced Science and Technology, 2020)
The main aim of the study is to find out the employee motivation and engagement in the Ancillary Industries of BHEL at Tiruchirapalli. The main relationship between the motivation and engagement is bind with that naturally, engaged employees are inherently motivated. These kinds of employees are always doing what they love. They also were applying their talents in an enthusiastic manner. Engaged employees encompass a wish or desire to help the company, and that is what motivates them. The study has been carried out on employees of Ancillary Industry of BHEL. In this study descriptive design and simple random sampling was used. The primary data was taken with the help of questionnaire for the study.